A Window as a Liminal Space (Victor Pelevin’s Hermit and Six-Toes) - Ochniak, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2022)
The window in Victor Pelevin’s works has numerous connotations, i.e. it is an element of the living space shaping the protagonist’s relationship with the outside world, defining his (i.e. the protagonist’s) position towards the world; it is a border (both spatial and ontological), as well as it is a link and a passage. Thus, the ambivalent characteristics of the window, its perception and feature all depend on the stance of a human beholder (or using literary terminology: a character, protagonist, and narrator) towards the window and his attitude towards the space with the window being its element. In Hermit and Six-Toes, the confined space in which the protagonists spend their entire lives is an oppressive territory, with the protagonists seeking a way to escape. The road to freedom leads, quite surprisingly, through a broken window, followed by a flight towards the sun. Thus, in this work, the window is treated as a threshold (liminal) zone, because a specific rite of passage and transformation of the characters takes place there or within. They grow to learn the truth and, rebelling in defence of their own lives, realise that they will either save themselves or succumb to the disastrous rhythm imposed on them by the world.